Efeito do tamanho de grão ultrafino nas propriedades mecânicas do aço Nb-Ti laminado a morno sequido de recozimento intercrítico e subcrítico - Hezio Rosa da Silva (2007)
In recent years there has been significant interest on developing of ultra fined ferrite grain steels in order to provide a grain refinement around 1 to 2 m, particularly low carbon Ti and Nb microalloyed steels. Several studies have been carried out by different methods such as; equal channel angular extrusion, accumulative roll-bonding and warm rolling, have shown that such grain refinement provides higher yield strengthand ultimate tensile strength aside from good toughness and lower ductile-brittle transition temperature. The aim of this work was a laboratory simulating of a possible industrial processing rout of a low carbon Ti and Nb microalloyed steel, in order to get an ultra fined ferrite grain size. Specimens of that material were submitted to quench and warm rolling, followed by intercritical and sub critical annealing. Such a processing rout was able to produce an ultra fined grain microstructure, which has developed a ferrite grain size among 2,05 and 3,48 m by submitting an intercritical annealing at 800 °C, and 1,64 m asannealing sub critically at 550 °C. Tensile and Charpy tests results have shown that such thermomechanical treatment rout is able to obtain a material having a good equilibrium among its mechanical properties; having presented ultimate tensile between 550 and 650 MPa, aside fromgood toughness and elongation. To all appearances, the material which has presented the best combination among strength, toughness and elongation has been annealing at 800 °C during 3600 s.